The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2174/1874350102013010242
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma, Reflective Functioning, and Problematic Mobile Phone Use Among Male and Female Adolescents

Abstract: Background: The association between traumatic experiences, different forms of emotion dysregulation and problematic technology uses is well established. However, little is known about the role of childhood traumatic experiences and reflective functioning in the onset and maintenance of mobile phone addiction symptoms among adolescents. Methods: Self-reported measures on childhood traumatic experiences, reflective functioning, and Problematic Mobile Phone Use (PMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 88 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…However, a moderate relationship was found. Another research done by Musetti et al [ 76 ] found a contradictory result between mobile phone addiction and playing video games. In particular, this research found a negative correlation between mobile gaming and mobile phone use among the female population in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a moderate relationship was found. Another research done by Musetti et al [ 76 ] found a contradictory result between mobile phone addiction and playing video games. In particular, this research found a negative correlation between mobile gaming and mobile phone use among the female population in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…The study was designed and carried out according to the Ethical Code of the Italian Association of Psychology (AIP), the European Code of Conduct for Research Integrity (ECCRI), and the 1964 Helsinki Declaration and its later amendments. The data presented in this study are part of a larger investigation on the relationship between childhood trauma and addictive behaviors among adolescents (Musetti, Brazzi, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to addictive behaviors, one cross-sectional study of 466 adolescents showed that a history of traumatic childhood experiences and uncertain reflective functioning were associated with higher levels of problematic mobile phone use, with females spending more time using mobile phones for social networking (Musetti, Brazzi, et al, 2020). To date, however, there is a lack of available studies on the relationship between CEA, reflective functioning, and problematic SNS use.…”
mentioning
confidence: 99%
“…Indeed, excessive media consumption and steady health messaging on COVID-19's diffusion and consequences are exacerbating factors on individuals' mental health (8). Previously, negative feelings have been extensively associated with excessive social media use and digital addiction (61)(62)(63)(64)(65)(66)(67)(68)(69)(70). In particular, loneliness is a risk factor related to problematic engagement in Internet-related activities (63,(71)(72)(73)(74)(75) and as one of the most important predictors of problematic Internet and social networking site use (76,77).…”
Section: Introductionmentioning
confidence: 99%